2016
DOI: 10.4236/cm.2016.72007
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of <i>Cornus officinalis</i> Total Glycosides and Cornus Polysaccharide on Myocardial Protection in Rats with Acute Myocardial Infarction

Abstract: Objective: To investigate effects of Cornus officinalis Total Glycosides (COTG) and Cornus Polysaccharide (CP) on myocardial protection and on expression of mitochondria biogenesis related gene of acute myocardial infarction (AMI) rats, Materials and Methods: Ninety-six SD rats of SPF level were randomly divided into 5 groups: sham operation group, model group, preventive treatment group, COTG treatment group, CP treatment group, and there were 12 cases in each one. By legating the left anterior descending bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…For thousands of years, Cor has been one of the most widely used medicinal plants in China and other East Asian countries to treat diseases, such as liver, kidney, and cardiovascular diseases and frequent urination (Hou et al, 2018). According to Chen et al (2015), the total glycosides and polysaccharides of Cor can improve cardiac function, reduce the area of acute myocardial infarction in rats, and promote the formation of myocardial mitochondria. In addition, Cor fruit core extract can reverse cardiac hypertrophy and improve cardiac functions (Fang et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…For thousands of years, Cor has been one of the most widely used medicinal plants in China and other East Asian countries to treat diseases, such as liver, kidney, and cardiovascular diseases and frequent urination (Hou et al, 2018). According to Chen et al (2015), the total glycosides and polysaccharides of Cor can improve cardiac function, reduce the area of acute myocardial infarction in rats, and promote the formation of myocardial mitochondria. In addition, Cor fruit core extract can reverse cardiac hypertrophy and improve cardiac functions (Fang et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies revealed that Cornus officinalis Total Glycosides, a promising cardioprotective Chinese herbs extract, inhibit cardiomyocyte apoptosis of suckling mouse in vitro [12] and improve myocardial ischemia injury by promoting mitochondrial biogenesis [8]. Mitochondria are important organelles for the energy supply of cardiac myocytes.…”
Section: Discussionmentioning
confidence: 99%
“…et Zucc., which have anti-inflammatory effects [7]. Our previous studies have been proved that Cornus officinalis Total Glycosides can improve myocardial ischemia injury by promoting mitochondrial biogenesis [8]. Nevertheless, it is unclear about the effect of Cornus officinalis…”
Section: Introductionmentioning
confidence: 99%
“…In a study utilizing an acute myocardial infarction (AMI) rat model to investigate the impact of C. officinalis polysaccharides on AMI rats, the results, compared with the model group, revealed an increase in left ventricular systolic pressure (LVSP) and a significant reduction in the myocardial infarction area. This suggests that C. officinalis polysaccharides play a crucial role in enhancing cardiac function and reducing the size of myocardial infarcts, possibly through the activation of the GSK-3β signaling pathway, imparting a cardioprotective effect ( 101 ). Furthermore, research has explored the antibacterial and antioxidant properties of polysaccharides derived from C. officinalis leaves.…”
Section: Bioactive Compounds In Cornus Officinalismentioning
confidence: 99%